Empirical Analysis of the Impact of the Internet on Social Trust in Chinese Provinces during 2016-2020 - Li Zhengrong; Guo Mengyao; Wang Fang (Redai dili)
The Internet, one of the hallmarks of information technology, has had a profound impact on social life, enriching public social activities while simultaneously altering traditional patterns of social trust formation. While academic attention has been given to the role of internet usage in shaping social trust, there remains a lack of further clarification regarding the spatiotemporal evolution of social trust across provinces in China under the influence of the Internet, as well as the differentiated effects of various internet usage patterns on social trust. This issue warrants further in-depth exploration to gain a more nuanced understanding of the dynamics. Based on data from the China Family Panel Studies between 2016 and 2020, this study constructs a theoretical framework to examine the impact of Internet usage patterns on social trust. Investigated the spatiotemporal evolution characteristics of social trust in China and used an Ordered Probit model to analyze the effects of different Internet usage methods on social trust. The findings reveal that the development of the Internet has created more possibilities for constructing social trust across various dimensions, thereby broadening the channels through which social trust is formed. Moreover, it has enriched the avenues through which both trust in strangers and acquaintances is generated, highlighting the role of the Internet in facilitating the establishment of trust within and beyond familiar social networks. Second, social trust in China is primarily based on trust among acquaintances. The levels of trust in acquaintances across the Eastern, Central, Western, and Northeastern regions exhibit a spatiotemporal evolution pattern of "low-high-low." Moreover, trust in strangers increased significantly over time across all regions. Overall, the level of social trust demonstrated an upward trend, indicating a general improvement in the willingness to trust both familiar and unfamiliar individuals across the country. Third, different internet usage methods have varying effects on social trust. The positive facilitation effect of information transmission benefits trust in acquaintances and strangers, contributing to higher levels of social trust. This suggests that the role of the Internet in disseminating information is crucial for fostering trust across various social groups. Fourth, the "dual-sided" effect of online social networking, as observed in this study, is manifested in its deleterious impact on trust within established social circles while simultaneously exerting a constructive influence on trust in individuals outside one's immediate network, thereby exemplifying the role of the Internet as a double-edged sword, where its capacity to both enhance and undermine trust depends on the nature of the interaction and the context in which it occurs. This study has significant implications for the scientifically sound and rational utilization of the positive role of the Internet as well as for balancing the development of information technology with social progress. This emphasizes the need to align technological advancement with the broader goals of fostering social trust and promoting social development.